2022
DOI: 10.4062/biomolther.2022.019
|View full text |Cite
|
Sign up to set email alerts
|

Benzyl Isothiocyanate-Induced Cytotoxicity via the Inhibition of Autophagy and Lysosomal Function in AGS Cells

Abstract: Gastric adenocarcinoma is among the top causes of cancer-related death and is one of the most commonly diagnosed carcinomas worldwide. Benzyl isothiocyanate (BITC) has been reported to inhibit the gastric cancer metastasis. In our previous study, BITC induced apoptosis in AGS cells. The purpose of the present study was to investigate the effect of BITC on autophagy mechanism in AGS cells. First, the AGS cells were treated with 5, 10, or 15 µM BITC for 24 h, followed by an analysis of the autophagy mechanism. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Similarly, BITC has been found to induce apoptosis in breast cancer cells but has no effect on normal breast MCF-10A cells [58]. These studies suggested that BITC has selective toxicity to tumor cells and is safe to use for cancer treatment [57][58][59]. BITC can effectively exert anticancer effects at concentrations (in vitro) or doses in vivo (in vivo animals) that are no-toxic to normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, BITC has been found to induce apoptosis in breast cancer cells but has no effect on normal breast MCF-10A cells [58]. These studies suggested that BITC has selective toxicity to tumor cells and is safe to use for cancer treatment [57][58][59]. BITC can effectively exert anticancer effects at concentrations (in vitro) or doses in vivo (in vivo animals) that are no-toxic to normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on BITC and AITC have shown that these compounds activate NRF2, a protein that controls the expression and induction of cytoprotective genes and induces the accumulation of autophagic molecules such as LC3BII and p62 in AGS cells [ 19 ]. In addition, it has been reported that BITC induced apoptotic cell death by inhibiting AKT in breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%